2015
DOI: 10.1111/clr.12570
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and treatment outcomes of dental implant‐related paranasal sinusitis: A 2‐year prospective observational study

Abstract: In our study, the majority of patients who once developed paranasal sinusitis associated with dental implants required surgical treatment. Findings of paranasal sinus CT may be important in determining treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 21 publications
0
52
1
5
Order By: Relevance
“…Sinonasal symptoms of ODS are consistent with cardinal symptoms of acute and chronic sinusitis, although ODS symptoms are more commonly unilateral . Anterior and posterior nasal drainage are most frequently reported in ODS in 60% or more of patients . Some series have reported foul smell or taste in 50% to 84% of ODS cases, whereas other series have reported foul smell or taste in a minority of cases .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Sinonasal symptoms of ODS are consistent with cardinal symptoms of acute and chronic sinusitis, although ODS symptoms are more commonly unilateral . Anterior and posterior nasal drainage are most frequently reported in ODS in 60% or more of patients . Some series have reported foul smell or taste in 50% to 84% of ODS cases, whereas other series have reported foul smell or taste in a minority of cases .…”
Section: Introductionmentioning
confidence: 79%
“…6,13,[15][16][17] Anterior and posterior nasal drainage are most frequently reported in ODS in 60% or more of patients. 6,15,16,18 Some series have reported foul smell or taste in 50% to 84% of ODS cases, 6,18 whereas other series have reported foul smell or taste in a minority of cases. 15,16 Dental symptoms are usually minimal to absent in ODS, 6,15,19 although Pokorny and Tataryn reported a 40% incidence of maxillary tooth pain in their series of predominantly endodontic-related ODS.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,17 In addition, rates of surgical intervention to address iatrogenic cases of odontogenic sinusitis may be as high as 80%. 11 Damage to the Schneiderian membrane of the sinus floor can occur with dental implants or foreign bodies, and this finding has also been associated with the need for surgical intervention. 11…”
Section: Etiologymentioning
confidence: 99%
“…The ostiomeatal unit is a functional unit involved in the drainage pathway for and ventilation of the maxillary, anterior ethmoid and frontal sinuses . Processes which impact the patency of the ostiomeatal unit may have an impact on the adjacent sinuses and have a significant impact on sinonasal disease …”
Section: Introductionmentioning
confidence: 99%
“…Mehra and colleagues found that, due to anatomical proximity of the maxillary sinus and adjacent teeth, approximately 10% of sinusitis is caused of dental origin. 13,14 The infected tooth apex with necrotic pulp may lead to sequential inflammations. 15 Evren and colleagues classified the relationship of the maxillary molars and sinus floor into 3 types according to the vertical distance of the molar roots to sinus floor.…”
mentioning
confidence: 99%